Sport system building and long-term athlete development in British Columbia - Balyi, I.
The objective of this paper is to shed some light on some of the key issues facing the British Columbian and Canadian sport systems. To achieve this objective, this paper will briefly: • describe British Columbia`s athlete development model, which has been accepted world wide and endorsed by the Coaching Association of Canada; • identify some of the major gaps in the current British Columbian and Canadian sport systems; • explain SportMap, a tool developed by British Columbia`s System Integration Group.